Expectations as a source of macroeconomic persistence: An exploration of firms' and households' expectation formation - Jeff Fuhrer (Federal Reserve Bank of Boston, 2015)
This paper examines the expectations behavior of individual responses in the surveys of the Survey of Professional Forecasters and the University of Michigan's Survey Research Center. The paper finds that respondents consistently revise their forecasts of inflation, unemployment, and other key variables so as to move them closer to the lagged central tendency of expectations in the survey. This result is quantitatively and statistically significant, and is robust to the inclusion of essentially all of the real-time information available in these surveys. The paper shows that rational agents with full information have no motive to link their current forecast to lagged central tendencies. This suggests that economic agents who do not know the true structure of the economy utilize a simple solution to a filtering problem, anchoring their forecasts to the most recently observed median forecast, which on average will contain important aggregated information about the variables they are attempting to forecast. This regularity bears important implications for macroeconomic dynamics, as illustrated in the last section of the paper. The regularity also provides a micro-based foundation for the paper's finding that expectations persistence is an important source of the macroeconomic persistence documented in Fuhrer (2015).
Keywords: E32; E52; 330; persistence; rational expectations; survey expectations